The incidence of the "Experiential Learning" as a strategy to teach vocabulary applied to basic computing science at 7th year of Basic Education, J.M. Jijón Elementary School, during the first term, 2007-2008 school year - Guasumba Pachacama, Yolanda del Pilar (2007)
After having spent for more than three years as students in the ESPE and as a requirement for our graduation in order to obtain our degree we had to carry out a thesis taking into account that a university thesis is the solution of a problem, and our problem was to find children in the Public schools in which they don't know vocabulary related to computing science, in order to give solution to this problem we have had to investigate techniques and Principles in Language Teaching, and Educational Psychology that complete our objectives, and we have chosen teaching method called Experiential Learning proposed by Dr. David Kolb as a strategy to carry out the aims. At the same time, we had to develop a Scientific investigation related to the computing science, once the information was in our hands the following steps were taken to make an innovative, easy, funny and pictorial handbook, without many complicated exercises, but, what it is more important, that fulfill the demands of the Kolb's cycle. Following this, We have chosen the institution in which we should put in practices this methodology, and this will be applied at 30 selected children at seven year of basic education of J.M. Jijon Caamaño y Flores School, located in Amaguaña town, province of Pichincha, during the first term, 2007-2008 school year. Then, with 30 students, divided into 2 groups: the first 15 students were the control group and others 15 were the experimental group, it is important to mention that the groups were not random assignment. In our research, the experimental method was considered, because it controls the conditions under which the scores and investigation are observed. The following step was the examination of all students, the instruments used as tool to be scored were: Diagnostic test at the beginning and Achievement test at the end of the program. The Diagnostic test was focused on the strengths and weaknesses of each student vis-?-vis the instructional objectives according to the needs analysis, taking into account that, A Needs Analysis is always the starting point for Experiential Learning program design. Taking into account that Need Analysis refers to the activities involved in gathering information that will serve as the basis for developing a programme that will meet the learning needs of a particular group of students...